Risk factors for thoracic aortic aneurysm and dissection among diabetic patients: a nationwide population-based study - Lim, Suk Kyung; Han, Kyungdo; Lee, Jun Ho; Lee, Kyu Na; Cho, In Young; Jin, Sang-Man; Sung, Kiick; Cho, Yang Hyun; Shin, Dong Wook (Frontiers in Cardiovascular Medicine, 2025)
BackgroundDiabetes mellitus (DM) has been reported to be associated with decreased risk for thoracic aortic aneurysm and dissection (TAAD). However, risk factors for TAAD in diabetic patients remain undetermined. This study aims to investigate diabetes-specific risk factors for TAAD development in diabetic patients.MethodsThis population-based study utilized the National Health Insurance Service database in Republic of Korea. We followed 2,328,347 type 2 DM patients undergoing health check-ups from 2009 to 2012 until new TAAD diagnosis, death, or December 31, 2019. Cox proportional-hazards regression models were used to identify risk factors for TAAD development.ResultsTAAD was newly diagnosed in 0.02% (4,512/2,328,347) of patients. In the fully-adjusted model incorporating baseline characteristics and antidiabetic medications, the risk for TAAD was increased with age (HR: 1.05, 95% CI: 1.05–1.06) and males (HR: 1.37, 95% CI: 1.26–1.49). Meanwhile, the risk of TAAD was decreased in patients with a longer diabetes duration (HR: 0.97, 95% CI: 0.96–0.99) and metformin use (HR: 0.91 95% CI: 0.85–0.97).ConclusionsOur study findings suggest that longer diabetes duration and metformin may reduce TAAD risk. Additional research is needed to investigate whether changes in glucose control and treatment strategies can decrease the development of TAAD in diabetic patients.